Luminescence studies on SnO2 and SnO2:Eu nanocrystals grown by laser assisted flow deposition. Issue 20 (28th May 2015) - Santos, N. F.; Rodrigues, J.; Holz, T.; Ben Sedrine, N.; Sena, A.; Neves, A. J.; Costa, F. M.; Monteiro, T.
<x xml:space="preserve">Abstract</x> Eu3+ optically-activated transparent conductive tin oxide nanocrystals were produced by the innovative laser assisted flow deposition technique.